2017
DOI: 10.1016/s2095-3119(16)61602-7
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the effects of urbanization on grain production and consumption in China

Abstract: The impact of rapid urbanization on food security of China has received considerable attention. It is not clear whether China can strike a balance between urbanization and food security, especially grain security. There have been numerous studies examining the effects of urbanization on grain production or consumption, but few studies have yet analyzed grain balances. Based on the Chinese World Agricultural Regional Market Equilibrium Model (CWARMEM), this paper explores the impacts of urbanization on national… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…However, such data were revised to 263.6 mmt in the China Statistical Yearbook 2018. Based on the revised statistical data, our balance sheet is different from Xu et al (2015), Lu et al (2017), andHuang et al (2017), which brings our forecast results closer to reality (Table 7).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…However, such data were revised to 263.6 mmt in the China Statistical Yearbook 2018. Based on the revised statistical data, our balance sheet is different from Xu et al (2015), Lu et al (2017), andHuang et al (2017), which brings our forecast results closer to reality (Table 7).…”
Section: Discussionmentioning
confidence: 73%
“…The figure would not exceed China's 7.2 mmt tariff rate quota. However, the simulation results from Lu et al (2017), Huang et al (2017), and PRIMAFF (2021) are larger than 7.2 mmt. Huang et al (2017) indicated that other studies might underestimate feed demand because they do not fully consider the rapid growth of maize used for processing, and they overestimate the gain from livestock feeding efficiency.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Wang et al (2018a) revealed that the spatial and temporal shift of grain yield occurred as a result of farmer-protecting grain subsidies and drastic improvements in agricultural infrastructure. On the other hand, factors such as environmental degradation (Huang and Rozelle, 1995), climate change, and landuse change induced by urbanisation (Lu et al, 2017) caused a reduction in the rate of grain yield growth. Porkka et al (2013) suggest that China's national demand for grain can be fulfilled by adjusting trade policies and importing more grain from foreign markets.…”
Section: The Impact Of the Supply Of Farmland Level Of Agricultural Mechanisation And Supply Of Rural Labour On Grain Yields In Chinamentioning
confidence: 99%
“…Therefore, protecting food security should focus not only on production, but also on retail and consumption [8,9]. In conclusion, research on food security in China has stepped into a completely new field and category [10,11]. Furthermore, statistics about per capita water and land resources and other limiting factors should be investigated, as should issues regarding resources and the environment caused by high-intensity grain production.…”
Section: Introductionmentioning
confidence: 99%